Analysis of Dengue Fever Spread Prediction Using Ensemble Learning Approach with Xgboost and Random - Maulana, Halim; Sari, Ayu Sekar (Bahasa Indonesia, 2024)
Dengue hemorrhagic fever (DHF) is a significant infectious disease in tropical countries, with a major public health impact. This study aims to develop a predictive model to estimate the number of dengue cases in two cities, San Juan and Iquitos, using the Random Forest and XGBoost algorithms. The dataset used is DengAI: Predicting Disease Spread, which includes various environmental and weather features such as temperature, rainfall, humidity, and vegetation index, as well as the number of dengue cases reported. The research process begins with data pre-processing to ensure data quality and suitability. After that, the predictive model was built using Random Forest and XGBoost. The model performance evaluation was carried out using Mean Absolute Error (MAE). The results showed that the XGBoost model had a better performance in predicting the number of dengue cases than the Random Forest model, with a lower MAE for both cities. The resulting predictive model can assist health authorities in planning and implementing more effective preventive measures. This study confirms the potential use of machine learning techniques in infectious disease epidemiology and provides important insights into environmental factors that influence the spread of dengue.